Homoeopathy in Diabetes Mellitus a Pancreatic Disease – Multimodal Lifestyle Intervention to its Complications (Homoeopathy for All, 2024)
The pancreas is an organ located  behind the lower part of the stomach,  in front of the spine and plays a vital  role in diabetes. In type 1 diabetes,  the beta cells of the pancreas no  longer make insulin because the  body’s immune system has attacked  them. In type 2 diabetes, the  pancreas loses the ability to secrete  enough insulin in response to meals.  Homoeopathy is considered as one  of the very best alternative system  for treating Diabetes Mellitus & its  complications. This article reviews  different complications of diabetes  mellitus with general management  and homoeopathic way of treatment.
Keywords: Homoeopathy; Pancreatic; Intervention